Conventional, Diffusion Weighted and Dynamic Contrast MRI in Evaluation of Oral Cavity and Pharyngeal Masses - Ahmed Sheta, Reham Samy; Dawoud, Rasha Mahmoud; Salama, Al-Siagy Ali; Maria, Alaa Mohamed; Elshafey, Khaled Ismail (Journal of Neonatal Surgery, 2025)
Background: The oral cavity is a complicated anatomical region that can be impacted by various disease masses. Proper diagnosis and grading of the mass is crucial for treatment plan and prognosis. The use of added sequences as diffusion weighted MRI (DWI) and dynamic contrast enhanced MRI (DCE) is supposed to offer more accuracy in differentiation and staging of the masses. The aim of the present work was to estimate the diagnostic value of multi-parametric MRI in evaluation of oral or pharyngeal masses. Methods: The prospective trial was carried out on 80 cases, aged from 18 to 62 years, both sexes, with suspected oral or pharyngeal mass. All patients were subjected to radiological and imaging evaluation including conventional MRI, DWI and DCE. Results: 26 cases were malignant in nature, two of them were lymphoma. 26 cases were benign including inflammatory masses. Recurrent lesions were found in 16 cases. Post-operative fibrosis in the tumor bed with negative malignancy in pathology was found in 12 cases. Overall accuracy for diagnosis of masses was higher using multi parametric MRI than conventional MRI with 95% and 85.15% respectively. For differentiation of recurrent or residual masses from post-operative fibrosis, Overall accuracy was 86.67% and 66.67% in multi parametric MRI and conventional MRI respectively. T and N staging systems were used for malignant masses. Accuracy of staging of the truly diagnosed cases was 80% using conventional MRI, and 91.6% using multiparametric MRI. For N staging, accuracy of conventional MRI was 80.3%. While accuracy of multipara metric MRI was 91.6%. Conclusions: Multi parametric MRI use can enhance the diagnostic accuracy of conventional MRI regarding nature of the masses, staging of malignant ones and discrimination of recurrent/ residual masses from post therapeutic changes.